2018
DOI: 10.3390/nu10091269
|View full text |Cite
|
Sign up to set email alerts
|

Association between Anaemia in Children 6 to 23 Months Old and Child, Mother, Household and Feeding Indicators

Abstract: In Low and Lower-Middle-Income countries, the prevalence of anaemia in infancy remains high. In early childhood anaemia cause irreversible cognitive deficits and represents a higher risk of child mortality. The consequences of anaemia in infancy are a major barrier to overcome poverty traps. The aim of this study was to analyse, based on a multi-level approach, different factors associated with anaemia in children 6–23 months old based on recent available Standard Demographic Health Surveys (S-DHS). We identif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
32
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 41 publications
13
32
5
1
Order By: Relevance
“…is finding was in line with previous studies [9,26]. e reason for this might be hemolysis of red blood cells that can be caused by febrile diseases like malaria.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…is finding was in line with previous studies [9,26]. e reason for this might be hemolysis of red blood cells that can be caused by febrile diseases like malaria.…”
Section: Discussionsupporting
confidence: 92%
“…is finding was congruent with studies carried out in Ethiopia [10,11,20], Brazil [25], Switzerland [26], Burma [27], and India [28]. e reasons for this might be low nutrition uptake among children from households with poor wealth index.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…10.2%) [5]. An observational study conducted in Switzerland reported that low birth weight raised the risk of anemia in infants aged 6-23 months by 16% [8]. Our study found no association between preterm birth or low birth weight with childhood anemia.…”
Section: Preterm Birth and Low Birth Weightcontrasting
confidence: 61%